2000
DOI: 10.1037/0278-6133.19.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Religious involvement and mortality: A meta-analytic review.

Abstract: A meta-analysis of data from 42 independent samples examining the association of a measure of religious involvement and all-eaase mortality is reported. Religious involvement was significantly associated with lower mortality (odds ratio = 1.29; 95% confidence interval: 1.20-1.39), indicating that people high in religious involvement were more likely to be alive at follow-up than people lower in religious involvement. Although the strength of the religious involvement-mortality association varied as a function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
509
7
22

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 833 publications
(574 citation statements)
references
References 72 publications
36
509
7
22
Order By: Relevance
“…1 Research has documented positive relationships between religious behavior and health, [2][3][4][5][6][7][8] and the majority of patients seem to want their physicians to be able to address the SR aspects of the illness experience. 9 -11 Although many physicians accept the idea that patient religiousness or spirituality can positively affect health, most do not initiate SR inquiry with patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Research has documented positive relationships between religious behavior and health, [2][3][4][5][6][7][8] and the majority of patients seem to want their physicians to be able to address the SR aspects of the illness experience. 9 -11 Although many physicians accept the idea that patient religiousness or spirituality can positively affect health, most do not initiate SR inquiry with patients.…”
mentioning
confidence: 99%
“…2 In addition, the life philosophy engendered by SR traditions (eg, feelings of optimism, love, hope, and solicitude) and the explanatory role of SR in providing meaning during existential crises (especially those prompted by loss of health and life) may have relevance to illness outcomes. 2 Overall, research on the prevalence of and recovery from physical and mental illness is more supportive of the positive role of SR in health than on its negative potential, [1][2][3][4][5][6][7][8] although it must be recognized that 1) some researchers have raised questions about the validity of this interpretation 17 and 2) these studies have not been done with pediatric populations.…”
mentioning
confidence: 99%
“…Several studies on religiosity and the relation with psychological well-being and mortality have found that the inclusion of variables of social support in the model significantly decreases the strength of this association, thus suggesting that social support may be an important mediator between religiosity and health. 1,5 Koenig et al, when examining social support and physical health as possible mediators between religiosity and depressive symptoms report that religious attendance was negatively associated with symptoms of depression and positively associated with physical health. 24 However, it was physical health instead of social support which appeared as the mediator between religion and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the inverse correlation between religiosity and mental disorders has been stronger in populations under stress-generating conditions such as physical disabilities and poverty. [1][2] In the present study, we adopted the concept of religion as an organized system of practices, rituals, beliefs and symbols that are designed to facilitate closeness to the sacred or transcendent, understanding spirituality as a personal quest for answers about the meaning of life and the relationship with the sacred or transcendent. While the different dimensions of religiosity can be investigated, the following dimensions are the most widely studied: subjective religiosity (how religious an individual considers himself to be), religious denomination (religion practiced by an individual) and organized religiosity (how often an individual goes to church and attends religious services or other religious activities).…”
Section: Investigating the Role Played By Social Support In The Assocmentioning
confidence: 99%
“…However, there are known protective factors, and alongside, for example, employment, social support and family connectedness, the role of religion has also been highlighted 3 . In part this relates to the benefits of religious participation for health outcomes generally 5 , but there is also international evidence of lower suicide rates among those of Roman Catholic faith compared to Protestants 6 (something of course also shown historically by Durkheim 7 ). One detailed study by Dorling and Gunnell 2 modelled the impact of particular social and economic factors (described as indicators of 'social isolation') on suicide rates in Britain in the last two decades of the 20 th Century.…”
mentioning
confidence: 98%